Inter-firm inventor movements and the optimal structure of co-inventor networks - Gergő Tóth; Balázs Lengyel (Hungarian Academy of Sciences, Institute of Economics, 2017)
There is a growing consensus that high impact innovation requires diverse knowledge access and cohesive groupwork at the same time; however, the role of social and collaboration networks in this phenomenon is still underexplored. In this paper we construct a weighted and time-decayed co-inventor network from all IT-related patents in the harmonized OECD PATSTAT 1977-2013 database. We look at the future impact of firm innovation and apply an inventor mobility framework for the 1990-2000 period to isolate the effect of inventor characteristics from the characteristics of the collaboration network in the firm. Our results imply that highest impact innovations are produced if the firm hires brokers who will work in cohesive networks in the firm. We find evidence that the small world property of networks within the firm exaggerates the effect of incoming brokers and high-impact inventors.
Keywords: C31; J69; O31; 330; co-inventor network; network constraint; small world network; patent citations; difference-in-differences; predicted margins